2015
DOI: 10.1016/s1701-2163(16)30033-0
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Contraception Consensus (Part 1 of 4)

Abstract: The quality of the evidence in this document was rated using the criteria described in the Report of the Canadian Task Force on Preventive Health Care (Table). Chapter 1: Contraception in Canada Summary Statements 1. Canadian women spend a significant portion of their lives at risk of an unintended pregnancy. (II-2) 2. Effective contraceptive methods are underutilized in Canada, particularly among vulnerable populations. (II-2) 3. Long-acting reversible contraceptive methods, including contraceptive implants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 0 publications
0
49
0
Order By: Relevance
“…Our findings further confirm that pharmacists have operationalized this label change in different ways. Black and Guilbert (2015) recently issued recommendations to address this issue, and our results suggest that the dissemination of evidence-based guidelines about the relationship between efficacy and weight, and a reminder to pharmacists that as an OTC product all people should be able to purchase the medication, is a priority.…”
Section: General Implicationsmentioning
confidence: 91%
“…Our findings further confirm that pharmacists have operationalized this label change in different ways. Black and Guilbert (2015) recently issued recommendations to address this issue, and our results suggest that the dissemination of evidence-based guidelines about the relationship between efficacy and weight, and a reminder to pharmacists that as an OTC product all people should be able to purchase the medication, is a priority.…”
Section: General Implicationsmentioning
confidence: 91%
“…E panding access to emergency contraception in Canada has long been identi ed as a priority among reproductive health and rights stakeholders [8,11,20]. urther, in recent years there has been a plethora of efforts in North merica to e pand access to long-acting, reversible contraception [21 23].…”
Section: Nmentioning
confidence: 99%
“…Methods of long-acting reversible contraception (LARC), including the hormonal intrauterine device (IUD), the Copper-T IUD, and implants, are safe and extremely effective at preventing pregnancies for 3-10 years [2]. In addition, the post-coital insertion of the Copper-T IUD is the most effective method of emergency contraception (EC) [3][4][5]. Insertion of the IUD within 7 days of unprotected or under-protected sexual intercourse represents an important option for women who not only want to prevent pregnancy after a specific event but also desire highly effective, ongoing contraception [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Findings on the role of hormonal contraceptives on breast cancer have not been consistent (Black et al, 2004). Using combined oral contraceptive pills as a prototype, earlier study did not find any association with breast cancer (CDC & NICHHD, 1986;Black et al, 2004); however, a collaborative group (CGHFBC, 1996) found a significant association though not when the pills have been stopped for more than 10years.…”
mentioning
confidence: 96%